The Gen Z preferences in choosing museum destinations: An analysis of E-WOM, destination image, and perceived value on the decision to visit the Jakarta Textile Museum - Ichwan Masnadi (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2024)
This research aims to investigate the effect of electronic word of mouth (E-WOM), destination image (DI), and perceived value (PV) on visit decision (VD) for Generation Z visitors in Jakarta Textile Museum. To determine the relationship between these variables, this research surveyed 238 Gen Z visitors using quantitative methods, including SEM analysis. The results revealed that perceived value mediates visit decisions and significantly affects them. E-WOM increases perceived value but has little impact on visit decisions. Conversely, destination image strongly influences the perceived value and visit decisions. The research emphasizes the need to improve the museum's image and value to attract Gen Z. It advises museum management to improve experiences, build emotional connections, and use E-WOM to boost their image. This is especially important in the digital age because Gen Z's decisions are largely impacted by internet information. Future studies should examine other visit decision elements and E-WOM in different circumstances.